Crisis Decision-Making at the Speed of COVID-19: Field Report on Issuing the First Regional Shelter-in-Place Orders in the United States. (January 2021) - Aragón, Tomás J.; Cody, Sara H.; Farnitano, Christopher; Hernandez, Lisa B.; Morrow, Scott A.; Pan, Erica S.; Tzvieli, Ori; Willis, Matthew
Abstract : Context: In March, 2020, the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the causal agent of coronavirus disease 2019 (COVID-19), was spreading in the Bay Area, especially in Santa Clara County, causing increases in cases, hospitalizations, and deaths. Program: The Association of Bay Area Health Officials (ABAHO) represents 13 Bay Area health jurisdictions. Implementation: On March 15, 2020, the local health officers of 7 ABAHO members (counties of Alameda, Contra Costa, Marin, San Francisco, San Mateo, and Santa Clara and the city of Berkeley) decided to issue legal orders on March 16 for 6.7 million residents to shelter in place to prevent the spread of SARS-CoV-2, the causal agent of COVID-19. The Bay Area was the first region in the United States to shelter in place, and within days, other regions in the United States followed. Evaluation: Subsequent comparative analyses have confirmed that acting early in issuing shelter-in-place orders prevented a large number of cases, hospitalizations, and deaths in the Bay Area throughout the United States. The quality of a decision—in this case, for crisis decision making—cannot be judged by the outcome. A good decision can have a bad outcome, and a bad decision can have a good outcome. The quality of a decision depends only on the quality of the decision-making process at the time the decision was made. Discussion: In this Field Report, we review how we made this collective decision. With the benefit of hindsight and reflection, we recount our story through the lens of public health legal authority, meta-leadership, and decision intelligence. Our purpose is to improve the crisis decision-making skills of public health officials by improving how we make high-stakes decisions each day in our continuing fight to contain the SARS-CoV-2 pandemic, to save lives, and to eliminate COVID-19 racial/ethnic inequities. Abstract : Supplemental Digital Content is Available in the Text.